LISTENING PROJECT: ACTIVE LISTENING WITH PATIENTS IN PALLIATIVE CARE - de Avila, Carolina Rasch; Pereira, Amanda Braga; Russo, Carolina Bartz; Vencato, Manuela de Faria Santos; Basso, Yasmin; Lopes, Caroline Vasconcellos (Seven Editora, 2026)
This paper presents an experience report on the EscutAção Project, developed by students from the Catholic University of Pelotas (UCPel), focusing on the application of active listening with patients under palliative care. The main objective of the initiative is to address the biopsychosocial demands of users from the Palliative Care Unit and the Outpatient Clinic of Integrative and Complementary Health Practices, providing a space for relief from psychosomatic suffering and strengthening the bond among professionals, patients, and their families. Partial results indicate a significant improvement in the emotional well-being of participants, a reduction in social isolation, and the identification of vulnerabilities such as family burden and domestic violence. For the extension students, the practice enables the development of communication skills, empathy, and professional ethics. Therefore, it is concluded that active listening constitutes a fundamental therapeutic and humanized tool, capable of promoting dignity and comprehensive health care in the face of life-limiting conditions.